Experimental seismocomplex “KNU-UkrSPl” and its purpose for decision of geological problems - ANDRUSHCHENKO, V.; KURHANSKYI, V.; ROMAN, V.; SYROTENKO, P.; TISHAIEV, I.; BUHRII, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Possibilites and destination of experimental seismocomplex "KNU-UkrSPI" are considered. Result of its tests and comparison with foreign analogues are shown.